Das Heroon von Trysa, 13 A Ein Denkmal in Lykien zwischen Ost und West: Untersuchungen zu Bildschmuck, Bauform und Grabinhaber - Landskron, Alice (Holzhausen, 2016)
The study examines the friezes of the Heroon of Trysa in context of Lycian culture and society and interprets the selection of the picture themes. In a very exceptional way the friezes visualize Greek, Lycian and Persian subjects and contents which characterize the world of the Lycians and meet the requirements of the tomb owner. The first part of the publication includes an introduction, the status of research, typological and iconographical analysis of the friezes, chapters on the style, the interpretation of the Heroon, and a catalogue, including description and technical information on the friezes and bibliographical abbrevations.The first part of the 2-volume publication includes an introduction, the status of research, typological and iconographical analysis of the friezes, chapters on the style, the interpretation of the Heroon, and a catalogue, including description and technical information on the friezes, and bibliographical abbreviations. http://e-book.fwf.ac.at/o:874 The second part includes images, supplements, tables, lists of images http://e-book.fwf.ac.at/o:875